Finance Carbon - Achmad, Andy; Khaddafi, Muammar (Sahabat Publikasi, 2024)
Negative externalities of carbon emissions are a global problem that requires government intervention to deal with. This research method uses a qualitative approach using the literature review method. The conclusion is that carbon finance is an important tool in global efforts to reduce greenhouse gas emissions and mitigate climate change. With a combination of carbon markets, public funding, and private investment, there are many opportunities to support projects that have a positive impact on the environment. However, to achieve success, the challenges of regulation, transparency, and market stability must be overcome.